Pengaruh Gigi Tiruan Lepasan (GTL) terhadap Kualitas Hidup Pasien Edentulous - Kamur, Imanuel Natalis; Maulida, Nurul Safira; Yuniar, Ainun Ayu; Tullah, Muh. Firdaus (Jurnal Terapi Gigi dan Mulut, 2025)
Tooth loss is a condition influenced by various factors, including caries, periodontal disease, trauma, and genetic factors, and it can significantly affect quality of life. The World Health Organization (WHO) reports that tooth loss remains a global health issue, with a prevalence of approximately 7% among individuals aged 20 years and older. In Indonesia, data from the 2025 health screening program indicate that approximately 37% of the population aged 0–60 years experience tooth loss. This study aimed to analyze the effect of removable dentures on the quality of life of edentulous patients at the Dental and Oral Health Education Hospital of Hasanuddin University. This study employed a descriptive quantitative cross-sectional design. A total of 30 edentulous patients aged 60–75 years, recorded in the Integration II register from July to August 2025, were selected using purposive sampling. Quality of life data were collected using a questionnaire and analyzed using simple linear regression with SPSS software. The results showed that the majority of respondents had a mean age of 65 years. Statistical analysis demonstrated a significant effect of removable denture use on the quality of life of edentulous patients (p = 0.028; α = 0.05). In conclusion, the use of removable dentures significantly improves the quality of life of edentulous patients.